Compact dual‐band bandpass filter with ultra‐wide upper‐stopband. Issue 11 (1st May 2013) - Wei, X.B.; Yue, G.T.; Liao, J.X.; Wang, P.; Xu, Z.Q.; Shi, Y.
Abstract : Proposed is a compact dual‐band bandpass filter (BPF) using stepped impedance resonators (SIRs). To improve the upper‐stopband of the proposed filter, tri‐section folded SIRs are used. By adjusting the impedance ratio and electronical length ratio of the tri‐section SIR, the out‐of‐band of the filter can be improved. A 2.09/2.62 GHz dual‐band experimental BPF has been designed and fabricated to demonstrate the proposed method. The measured results are in good agreement with the electromagnetic simulation. The spurious frequencies of the upper‐stopband are suppressed below 20 dB from 2.79 to 22.13 GHz. The circuit only occupies 0.29 λg × 0.13 λg.